2022
DOI: 10.3897/biorisk.17.77488
|View full text |Cite
|
Sign up to set email alerts
|

Organic vs conventional farming of oil-bearing rose: Effect on essential oil and antioxidant activity

Abstract: The aim of this study was to establish whether the type of the agricultural system has any influence on the essential oil production and antioxidant activity of industrial cultivated Rosa damascena Mill. in the Rose valley, Bulgaria. Six private farms from Kazanlak (Rose) Valley, Southern Bulgaria were included in the study conducted in the period 2019–2020. The first three selected farms are designated within the conventional farming and the other three are certificated as organic farms. GC/FID and GC/MS anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recent meta-analyses have shown that organic production methods tend to significantly increase antioxidants, phenols, and Zn compared to conventional farming [37]. Additionally, when roses were cultivated through organic farming, they exhibited superior antioxidant effects compared to those grown conventionally [38]. In this study, organically grown OB and NB also showed higher DPPH scavenging ability than CB, and in particular, the antioxidant properties of NB were superior to those of CB and OB with increasing concentration.…”
Section: Discussionmentioning
confidence: 50%
“…Recent meta-analyses have shown that organic production methods tend to significantly increase antioxidants, phenols, and Zn compared to conventional farming [37]. Additionally, when roses were cultivated through organic farming, they exhibited superior antioxidant effects compared to those grown conventionally [38]. In this study, organically grown OB and NB also showed higher DPPH scavenging ability than CB, and in particular, the antioxidant properties of NB were superior to those of CB and OB with increasing concentration.…”
Section: Discussionmentioning
confidence: 50%
“…The essential oil from organic farming provides higher linalool and geraniol content and lower β-citronellol + nerol concentrations than conventional farming. It has also been found that combining ecofriendly agricultural practices in organic private farms for damask rose cultivation resulted in higher antioxidant activity values in rose phytoconstituents from rose methanolic extracts compared to those from conventional agricultural systems [68].…”
Section: Agronomic Aspects Influencing the Biosynthesis Of Aromatic C...mentioning
confidence: 99%
“…Essential oil composition is determined by the plant genotype, but abiotic factors and growing conditions can also affect biomass production and oil quality. For example, the team of Todorova et al (2022) [13] found that the type of agrarian production system has no influence on the chemical composition of the rose oil from the R. Damascena oil-bearing plant, but the highest productivity of essential oil was obtained in combined ecological agricultural practices (low-input farming system)-0.039%, followed by typical conventional farming-0.036% and the lowest productivity was obtained from rose plantations grown through organic farming-0.030%. The study by Ghrysargyris et al (2016) [14] in hydroponic cultivation of L. angustifolia Mill.…”
Section: Introductionmentioning
confidence: 99%